IMMU-10. GENOMIC DIFFERENCES UNDERLIE MYELOID-DERIVED SUPPRESSOR CELL SEXUAL DIMORPHISM IN GLIOBLASTOMA. (9th November 2020) - Bayik, Defne; Zhou, Yadi; Lo, Alice; Park, Chihyun; Hong, Changjin; Vail, Daniel; Watson, Dionysios; Roversi, Gustavo; Lauko, Adam; Silver, Daniel; Alban, Tyler; Otvos, Balint; et al.
Abstract: A potently immunosuppressive tumor microenvironment facilitates progression of glioblastoma (GBM). We previously demonstrated that myeloid-derived suppressor cell (MDSC) subsets promote tumorigenesis in a sex-specific manner, contributing to sexual dimorphism in GBM incidence and prognosis. Our findings indicated that proliferating monocytic MDSCs (mMDSCs) accumulate in tumors of male mice and patients, while female tumor-bearing mice had an increase in circulating granulocytic MDSC (gMDSC) frequency, and a high gMDSC gene signature correlated with worse outcome of female patients. However, the mechanisms underlying sexual dimorphism of MDSC heterogeneity remain understudied and can provide insights for improved immunotherapy response. Using syngeneic mouse glioma models and sequencing approaches, we show that expression of Y-chromosome-linked genes correlates with upregulation of multiple RNA transcription-related pathways specifically in male mMDSCs. Consistently, adoptive transfer of male mMDSCs but not gMDSCs worsened GBM outcome in male recipients, while the transfer of sex-matched mMDSCs did not impact survival of female mice. In contrast to this cell-intrinsic regulatory pathway, sex steroids had no impact on MDSC profile, as castration or ovariectomy failed to alter MDSC subset accumulation patterns in GBM-bearing mice. Correspondingly, IL-1β, which we had identified as a female-specific drug target, was highly expressed in female but not male gMDSCs. Single-cell sequencing revealed that circulating but not tumor-infiltrating gMDSCs were the primary source of IL-1β and that its neutralization provided a female-specific survival advantage by reducing circulating gMDSCs. This was accompanied by declines in tumor infiltration of microglia, microglia activation status and tumor cell proliferation. In vitro, IL-1β inhibition reduced viability and expression of activation markers by primary microglia. These findings highlight a peripheral gMDSC-microglia communication axis mediated by IL-1β signaling in females with GBM and indicate that expression differences in MDSC subsets represent opportunities for improved immunotherapy efficacy while accounting for sex as a biological variable.